5-Sulfoisophthalic acid tetrahydrate and its manufacturing method

By suspending crude 5-sulfoisophthalic acid in water and incubating at 34°C or lower, the method effectively reduces sulfuric acid impurities in 5-sulfoisophthalic acid, producing high-purity 5-sulfoisophthalic acid tetrahydrate crystals with improved filterability.

JP7659310B2Active Publication Date: 2025-04-09KONISHI CHEM IND
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021151428
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-16
Publication Date
2025-04-09
Estimated Expiration
2041-09-16

AI Technical Summary

Technical Problem

Existing methods for producing 5-sulfoisophthalic acid result in high sulfuric acid impurity content, which is difficult to remove completely using acetic acid, lithium salts, or organic solvents, leading to these substances remaining as impurities.

Method used

A method involving the suspension or crystallization of crude 5-sulfoisophthalic acid in water, followed by incubation at 34°C or lower for 5 minutes or more, effectively reduces sulfuric acid content without using acetic acid or organic solvents, resulting in the formation of novel 5-sulfoisophthalic acid tetrahydrate crystals.

Benefits of technology

This method achieves a significant reduction in sulfuric acid content to 2.0% by mass or less, eliminating the need for impurity substances and improving the purity and filterability of 5-sulfoisophthalic acid tetrahydrate crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659310000003
    Figure 0007659310000003
  • Figure 0007659310000004
    Figure 0007659310000004
  • Figure 0007659310000005
    Figure 0007659310000005
Patent Text Reader

Abstract

To provide 5-sulfoisophthalic acid and a method for producing the same in which the content of sulfuric acid as an impurity is reduced and there is no problem that substance used to reduce a sulfuric acid content remains as an impurity.SOLUTION: The problem is solved by 5-sulfoisophthalic acid tetrahydrate and a method for producing the same that is obtained by a production process including a step in which crude 5-sulfoisophthalic acid is purified by a specific method using water.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to 5-sulfoisophthalic acid tetrahydrate and a method for producing the same. [Background technology]

[0002] 5-Sulfoisophthalic acid is generally obtained by, for example, reacting isophthalic acid with fuming sulfuric acid or the like to sulfonate the isophthalic acid (e.g., Patent Documents 1 to 3). Therefore, 5-sulfoisophthalic acid contains sulfuric acid as an impurity (e.g., Non-Patent Document 1, Patent Documents 2 and 3).

[0003] For example, Non-Patent Document 1 describes that 5-sulfoisophthalic acid contains 3% by weight of sulfuric acid. Patent Document 2 describes that as a result of a method for producing 5-sulfoisophthalic acid having a product precipitation step using a 30% to 40% sulfuric acid solution, the sulfate level in 5-sulfoisophthalic acid monolithium salt obtained from the 5-sulfoisophthalic acid is 1000 ppm to 3000 ppm. In addition, it describes that in order to reduce the sulfate level, acetic acid, water, a lithium cation generating compound, and 5-sulfoisophthalic acid are mixed and heated. In addition, Patent Document 3 describes that it has been difficult to remove sulfuric acid, which is an impurity, from 5-sulfoisophthalic acid, and that the sulfuric acid content can be reduced by mixing and stirring crude 5-sulfoisophthalic acid with an organic solvent containing an aliphatic ketone and / or alicyclic ketone, and then isolating 5-sulfoisophthalic acid from the organic solvent by solid-liquid separation. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-331527 A [Patent Document 2] Special Publication No. 2013-508377 [Patent Document 3] German Patent Application Publication DE2804330A1 [Non-patent literature]

[0005] [Non-Patent Document 1] Zhurnal Strukturnoi Khimii 1989,30(3),174. Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned conventional techniques use acetic acid and a lithium salt or an organic solvent to reduce the sulfuric acid content, and therefore have the problem that these remain as impurities.

[0007] An object of one aspect of the present invention is to provide 5-sulfoisophthalic acid, which has a reduced sulfuric acid content as an impurity and is free of the problem that substances used to reduce the sulfuric acid content remain as impurities, and a method for producing the same. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the present inventors have surprisingly found that when crude 5-sulfoisophthalic acid is purified by a specific method using water, the sulfuric acid content can be reduced without using acetic acid or an organic solvent. Furthermore, X-ray crystal structure analysis has revealed that the obtained 5-sulfoisophthalic acid is a novel 5-sulfoisophthalic acid tetrahydrate that had not been known before, and have thus completed the present invention. That is, the present invention includes the following aspects.

[0009] [1] 5-Sulfoisophthalic acid tetrahydrate.

[0010] [2] A crystal of 5-sulfoisophthalic acid tetrahydrate according to [1].

[0011] [3] A crystal of 5-sulfoisophthalic acid tetrahydrate according to [2], in which the crystal space group is P-1 (where "-" indicates an overline of 1), the unit cell has lattice constants a = 7.139(2) Å, b = 9.490(3) Å, c = 10.535(3) Å, α = 70.999(7)°, β = 77.158(7)°, and γ = 85.530(8)°.

[0012] [4] A crystal of 5-sulfoisophthalic acid tetrahydrate according to [2] or [3], having a sulfuric acid content of 2.0% by mass or less.

[0013] [5] A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate, comprising a step of suspending or crystallizing a crude product containing 5-sulfoisophthalic acid monohydrate in water.

[0014] [6] A method for producing the crystals of 5-sulfoisophthalic acid tetrahydrate according to [5], comprising a step of suspending a crude product containing 5-sulfoisophthalic acid monohydrate in water and incubating the suspension at 34°C or lower for 5 minutes or more.

[0015] [7] A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to [5], comprising the steps of: dissolving a crude product containing 5-sulfoisophthalic acid monohydrate in water at a temperature of 34°C to 104°C; cooling the aqueous solution obtained in the above step; and adding seed crystals of 5-sulfoisophthalic acid tetrahydrate when the aqueous solution is at 38°C or lower and in a supersaturated state or in a state in which crystals have precipitated, thereby obtaining crystals of 5-sulfoisophthalic acid tetrahydrate. Effect of the Invention

[0016] According to one aspect of the present invention, it is possible to provide 5-sulfoisophthalic acid, crystals of 5-sulfoisophthalic acid, and a method for producing the same, in which the content of sulfuric acid as an impurity is reduced and there is no problem that a substance used to reduce the content of sulfuric acid remains as an impurity. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows a powder X-ray diffraction pattern of the crystals of 5-sulfoisophthalic acid tetrahydrate obtained in Example 1. [Diagram 2] FIG. 2 is a diagram showing a powder X-ray diffraction pattern of the crystals of 5-sulfoisophthalic acid tetrahydrate obtained in Example 2. [Diagram 3] FIG. 3 is an ORTEP diagram obtained by single crystal X-ray structure analysis of the crystal of 5-sulfoisophthalic acid tetrahydrate obtained in Example 2. [Figure 4] FIG. 4 is a molecular packing diagram obtained by single crystal X-ray structure analysis of the crystal of 5-sulfoisophthalic acid tetrahydrate obtained in Example 2. [Diagram 5] FIG. 5 shows the results of thermogravimetry of the crystals of 5-sulfoisophthalic acid tetrahydrate obtained in Example 2. [Figure 6] FIG. 6 is a diagram showing an example of a method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention. [Figure 7] FIG. 7 is a diagram showing an example of a method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention. [Figure 8] FIG. 8 is a diagram showing a powder X-ray diffraction pattern of the crystals of 5-sulfoisophthalic acid monohydrate obtained in Comparative Example 1. [Figure 9] FIG. 9 is an ORTEP diagram obtained by single crystal X-ray structure analysis of the crystal of 5-sulfoisophthalic acid monohydrate obtained in Comparative Example 1. [Figure 10] FIG. 10 is a molecular packing diagram obtained by single crystal X-ray structure analysis of the crystal of 5-sulfoisophthalic acid monohydrate obtained in Comparative Example 1. [Figure 11] FIG. 11 shows the results of thermogravimetry of the crystals of 5-sulfoisophthalic acid monohydrate obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] [1] 5-Sulfoisophthalic acid tetrahydrate The present inventors have found that when crude 5-sulfoisophthalic acid is purified by a specific method of suspending or crystallizing it in water, crystals with a reduced sulfuric acid content are obtained. Furthermore, by X-ray crystal structure analysis of the crystals, the inventors have found that the obtained 5-sulfoisophthalic acid is a novel 5-sulfoisophthalic acid tetrahydrate that has not been known before. That is, one aspect of the present invention is 5-sulfoisophthalic acid tetrahydrate. Another embodiment of the present invention is a crystal of 5-sulfoisophthalic acid tetrahydrate.

[0019] In 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention, the 5-sulfoisophthalic acid purity is preferably 62% by mass to 78% by mass, more preferably 67% by mass to 78% by mass, and further preferably 73% by mass to 77% by mass. Note that the "5-sulfoisophthalic acid purity" here means the purity of 5-sulfoisophthalic acid (excluding water of crystallization) contained in the crystals, and is a value measured by the method described in the Examples.

[0020] The sulfuric acid content in 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, and further preferably 0.5% by mass or less. Conventionally, in applications such as polymer additives of metal salts of 5-sulfoisophthalic acid and 5-sulfoisophthalic acid esters produced from 5-sulfoisophthalic acid as a raw material, sulfuric acid contained as an impurity has been a problem. Since the sulfuric acid content in the crystals of 5-sulfoisophthalic acid tetrahydrate is reduced, the problem of sulfuric acid contained in metal salts of 5-sulfoisophthalic acid and 5-sulfoisophthalic acid esters can be solved. The "sulfuric acid content" here is a value measured by the method described in the Examples.

[0021] The Hazen color unit number of an aqueous solution of 50% by mass of 5-sulfoisophthalic acid obtained by dissolving 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention in water is preferably 200 or less, more preferably 180 or less, and even more preferably 160 or less. The lower limit of the Hazen color unit number is 10. The Hazen color unit number of 200 or less can reduce coloration of crystals. Therefore, it is possible to reduce impurities that cause coloration of 5-sulfoisophthalic acid and industrial products made from 5-sulfoisophthalic acid. The "Hazen color unit number" here is a value measured by the method described in the Examples.

[0022] The average particle size of the crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention is preferably 50 μm to 2500 μm, more preferably 100 μm to 2000 μm, and further preferably 150 μm to 1600 μm. When the average particle size is within the above range, filterability is improved. In addition, there is an effect that the adhesion of mother liquor to the crystals is reduced, thereby improving the quality of 5-sulfoisophthalic acid. Here, the "average particle size" of the crystals is a value measured by the method described in the Examples.

[0023] The crystal of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention may have a space group of P-1 (where "-" indicates an overline of 1), and the unit cell may have lattice constants of a = 7.139(2) Å, b = 9.490(3) Å, c = 10.535(3) Å, α = 70.999(7)°, β = 77.158(7)°, and γ = 85.530(8)°. The values ​​in parentheses indicate standard deviations.

[0024] The crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention have characteristic peaks at the following 2θ angles in a powder X-ray diffraction spectrum: 18.2±0.2°, 20.3±0.2°, 24.7±0.2°, 27.4±0.2°, 30.5±0.2°, and 32.0±0.2°.

[0025] The crystal shape of the 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention may be columnar.

[0026] The results of thermogravimetry (TG) of the crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention show that the peaks that begin to absorb heat at around 27° C. and around 49° C. show a mass loss of three equivalents of water molecules relative to 5-sulfoisophthalic acid, and the peak that begins to absorb heat at around 142° C. shows a mass loss of one equivalent of water molecules relative to 5-sulfoisophthalic acid. In this specification, "around" means ±5° C.

[0027] [2] Method for preparing crystals of 5-sulfoisophthalic acid tetrahydrate 5-Sulfoisophthalic acid tetrahydrate or a crystal thereof according to one embodiment of the present invention can be produced by suspending or crystallizing a crude product containing 5-sulfoisophthalic acid monohydrate in water. Thus, the present invention also includes a method for producing a crystal of 5-sulfoisophthalic acid tetrahydrate, which comprises a step of suspending or crystallizing a crude product containing 5-sulfoisophthalic acid monohydrate in water.

[0028] According to the above-mentioned production method including the step of suspending or crystallizing in water, it is possible to obtain crystals of 5-sulfoisophthalic acid tetrahydrate with a reduced sulfuric acid content without using acetic acid, lithium salts, organic solvents, etc. Therefore, there is no problem of acetic acid, lithium salts, organic solvents, etc. remaining as impurities. Furthermore, since no organic solvents are used, the burden on the environment can be reduced, which can contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns."

[0029] [2.1] Manufacturing method including a step of suspending in water A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention may include a step of suspending a crude product containing 5-sulfoisophthalic acid monohydrate in water and incubating the suspension at 34° C. or lower for 5 minutes or more.

[0030] The crude product containing 5-sulfoisophthalic acid monohydrate is a crude product obtained by the synthesis of 5-sulfoisophthalic acid, and usually contains 5-sulfoisophthalic acid monohydrate. It is preferable to use the crude product which is once extracted as crystals (crude crystals).

[0031] 6 shows an example of the method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to this embodiment. The crude product is suspended in water. The amount of water in which the crude product is suspended is not particularly limited as long as the crude product is suspended without being completely dissolved, but is preferably 0.19 to 0.60 times by mass, more preferably 0.28 to 0.55 times by mass, and even more preferably 0.35 to 0.50 times by mass relative to the amount of 5-sulfoisophthalic acid (excluding water of crystallization) in the crude product.

[0032] The temperature of the water in which the crude product is suspended is not particularly limited as long as the crude product is suspended without being completely dissolved, but is preferably −20° C. to 34° C., more preferably 0° C. to 30° C., and even more preferably 7° C. to 25° C. If the temperature of the water in which the crude product is suspended is −20° C. or higher, the solution in which the crude product is suspended does not freeze, which is preferable. In addition, if the temperature of the water in which the crude product is suspended is 34° C. or lower, the time required for 5-sulfoisophthalic acid tetrahydrate to be generated is short, which is preferable.

[0033] The method of suspending the crude product in water is not particularly limited, and for example, the crude product may be poured into water or water may be added to the crude product, but it is more preferable to pour the crude product into water, and further more preferable to pour the crude product into water while stirring.

[0034] Thereafter, the crude product is suspended in water and the resulting suspension is kept at 34°C or lower for 5 minutes or more. By keeping the suspension at 34°C or lower, it is possible to obtain crystals of 5-sulfoisophthalic acid tetrahydrate with good filterability. The temperature at which the suspension is kept is not particularly limited as long as it is 34°C or lower, but is more preferably 30°C or lower, and even more preferably 25°C or lower. The lower limit of the temperature at which the suspension is kept is also not particularly limited as long as it is -20°C or higher, but is more preferably 0°C or higher, and even more preferably 7°C or higher.

[0035] By keeping the suspension at 34°C or less for 5 minutes or more, it is possible to obtain crystals of 5-sulfoisophthalic acid tetrahydrate with good filterability. The time for keeping the suspension at 34°C or less is more preferably 15 minutes or more, and even more preferably 30 minutes or more. The upper limit of the keeping time is not limited to this, but is preferably 12 hours or less from the viewpoint of production efficiency. From the viewpoint of obtaining crystals of 5-sulfoisophthalic acid tetrahydrate with good filterability, it is more preferable that the keeping temperature is constant throughout the entire keeping time, but the temperature may vary as long as it is within the above-mentioned temperature range.

[0036] The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to the present embodiment may further include a step of filtering the crystals of 5-sulfoisophthalic acid tetrahydrate obtained by the above step. The method for filtering the crystals of 5-sulfoisophthalic acid tetrahydrate is not particularly limited, and examples of the method include filtration using a normal filter medium, filtration such as centrifugal filtration, pressure filtration, and reduced pressure filtration.

[0037] The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to the present embodiment may further include a synthesis step of synthesizing 5-sulfoisophthalic acid to obtain a crude product containing 5-sulfoisophthalic acid monohydrate. The synthesis step is also not particularly limited, but an example of the synthesis step is a method of reacting isophthalic acid with fuming sulfuric acid or the like to sulfonate isophthalic acid, as shown in the following formula.

[0038] [ka]

[0039] For example, after the sulfonation, the reaction product is dropped into water and the precipitated crystals are filtered to obtain hydrated crystals of 5-sulfoisophthalic acid monohydrate. The hydrated crystals can be used as a crude product containing 5-sulfoisophthalic acid monohydrate.

[0040] [2.2] Manufacturing method including a step of crystallization in water A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to one embodiment of the present invention may include the steps of: (a) dissolving a crude material containing 5-sulfoisophthalic acid monohydrate in water at a temperature of 34°C to 104°C; (b) cooling the aqueous solution obtained in the step (a); and (c) adding seed crystals of 5-sulfoisophthalic acid tetrahydrate to crystallize the aqueous solution when the aqueous solution is at 38°C or lower and in a supersaturated state or in a state where crystals are precipitated, thereby obtaining crystals of 5-sulfoisophthalic acid tetrahydrate. Although precipitation may occur without adding seed crystals, it is industrially preferable to add them. FIG. 7 shows an example of a method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to this embodiment.

[0041] <Process (a)> The crude product containing 5-sulfoisophthalic acid monohydrate is as explained in the production method including the step of suspending in water mentioned above, and therefore the explanation will be omitted here.

[0042] In the step of dissolving a crude product containing 5-sulfoisophthalic acid monohydrate in water at a temperature of 34°C to 104°C, it is preferable that 5-sulfoisophthalic acid monohydrate is completely dissolved, but it is not essential that a portion of the 5-sulfoisophthalic acid monohydrate is not dissolved.

[0043] Incidentally, "dissolving in water at a temperature of 34°C to 104°C" means bringing the crude product into a dissolved state at 34°C to 104°C, and also includes the case where the aqueous solution obtained by dissolving the crude product in water at a temperature lower than 34°C is heated to bring the crude product into a dissolved state at 34°C to 104°C.

[0044] For example, as shown in Fig. 7, a method of dissolving 5-sulfoisophthalic acid monohydrate by suspending the crude product in water and heating the resulting suspension to 34°C to 104°C can be suitably used. Alternatively, the crude product can be dissolved in water heated to 34°C to 104°C.

[0045] The amount of water in which the crude product is dissolved is not particularly limited, but is preferably 0.19 to 0.60 times by mass, more preferably 0.28 to 0.55 times by mass, and even more preferably 0.35 to 0.50 times by mass relative to the amount of 5-sulfoisophthalic acid (excluding water of crystallization) in the crude product.

[0046] The temperature at which 5-sulfoisophthalic acid monohydrate is dissolved in water may be 34°C to 104°C, more preferably 45°C to 95°C, and even more preferably 60°C to 80°C. If the temperature at which 5-sulfoisophthalic acid monohydrate is dissolved in water is 34°C or higher, the particle size of the resulting 5-sulfoisophthalic acid tetrahydrate will be large, which is preferable. If the temperature at which 5-sulfoisophthalic acid monohydrate is dissolved in water is 104°C or lower, the temperature can be raised under normal pressure, which is preferable.

[0047] In order to dissolve 5-sulfoisophthalic acid monohydrate in water at a temperature of 34°C to 104°C, the crude product may be suspended in water and the resulting suspension may be heated to 34°C to 104°C, or the crude product may be poured into water at 34°C to 104°C, and the resulting solution may be kept at that temperature.

[0048] <Process (b)> The cooling method in step (b) for cooling the aqueous solution at 34°C to 104°C obtained in step (a) is not particularly limited, and examples of the cooling method include natural cooling, cooling using a water bath, and cooling using brine.

[0049] The cooling rate is not particularly limited, but is preferably 20° C. / hour or less, more preferably 10° C. / hour or less, and further preferably 5° C. / hour or less. A cooling rate within the above range is preferable because it allows the crystals of 5-sulfoisophthalic acid tetrahydrate to be obtained with a large particle size.

[0050] <Process (c)> When the aqueous solution cooled in step (b) is at 38° C. or lower and is in a supersaturated state or crystals are precipitated, seed crystals of 5-sulfoisophthalic acid tetrahydrate can be added to the aqueous solution to cause crystallization, thereby obtaining crystals of 5-sulfoisophthalic acid tetrahydrate.

[0051] As the seed crystals of 5-sulfoisophthalic acid tetrahydrate, crystals of 5-sulfoisophthalic acid tetrahydrate obtained by the above-mentioned production method including a step of suspending in water can be used.

[0052] The seed crystals are added when the aqueous solution is supersaturated or crystals are precipitated and at 38° C. or lower, more preferably 37° C. or lower, and even more preferably 35° C. or lower. Adding the seed crystals at this stage can change the form of the plate crystals partially precipitated in step (b) to columnar crystals, producing 5-sulfoisophthalic acid tetrahydrate. If seed crystals are not added, the slurry viscosity increases, making stirring and filtration difficult.

[0053] The amount of the seed crystals to be added is not particularly limited, but is preferably 0.1 ppm to 10 mass % relative to the amount of 5-sulfoisophthalic acid (excluding water of crystallization) in the crude product, more preferably 1.0 ppm to 1.0 mass %, and even more preferably 10 ppm to 0.1 mass %. If the amount of the seed crystals is 0.1 ppm or more, 5-sulfoisophthalic acid tetrahydrate is precipitated in a short time, which is preferable. Also, if the amount of the seed crystals is 10 mass % or less, crystals of 5-sulfoisophthalic acid tetrahydrate grow large, which improves filterability, which is preferable.

[0054] After the seed crystals are added, it is preferable to continue cooling the aqueous solution. By continuing the cooling, 5-sulfoisophthalic acid tetrahydrate is produced in a short time. It is preferable to continue cooling until the aqueous solution reaches a temperature of preferably -20°C to 34°C, more preferably 0°C to 30°C, and even more preferably 7°C to 25°C.

[0055] The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to the present embodiment may further include a step of filtering the crystals of 5-sulfoisophthalic acid tetrahydrate obtained by the above-mentioned step. The filtration method is the same as that of the above-mentioned production method including a step of suspending in water, and therefore the explanation thereof will be omitted.

[0056] The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to this embodiment may further include a synthesis step of synthesizing 5-sulfoisophthalic acid to obtain a crude product containing 5-sulfoisophthalic acid monohydrate. This step is similar to the above-mentioned production method including the step of suspending in water, so a description thereof will be omitted.

[0057] According to the production method of this embodiment, it is possible to obtain crystals of 5-sulfoisophthalic acid tetrahydrate with a particularly large average particle size. The average particle size of the crystals of 5-sulfoisophthalic acid tetrahydrate obtained by the production method of this embodiment is preferably 200 μm to 2500 μm, more preferably 400 μm to 2000 μm, and further preferably 500 μm to 1600 μm.

[0058] Furthermore, according to the production method of this embodiment, it is possible to obtain crystals of 5-sulfoisophthalic acid tetrahydrate with reduced coloration. The Hazen color unit number of an aqueous solution of 5-sulfoisophthalic acid having a concentration of 50% by mass, obtained by dissolving 5-sulfoisophthalic acid tetrahydrate obtained by the production method of this embodiment in water, is preferably 200 or less, more preferably 180 or less, and even more preferably 50 or less. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0060] [Measurement method] <5-Sulfoisophthalic acid purity and sulfuric acid content> The purity of 5-sulfoisophthalic acid and the content of sulfuric acid in the wet cake of 5-sulfoisophthalic acid (hydrated crystals obtained by centrifugal filtration) were measured by the following method. First, 1.5 g of the wet cake was precisely weighed and dissolved in 80 mL of N,N-dimethylformamide. The obtained solution was titrated with 1 mol / L aqueous sodium hydroxide solution using an automatic titrator (HIRANUMA Co., Ltd., model: COM-1750), and the purity of 5-sulfoisophthalic acid and the content of sulfuric acid were measured by detecting the inflection point.

[0061] The sulfuric acid content of the wet cake of 5-sulfoisophthalic acid having a sulfuric acid content of 1 mass% or less was measured using ion chromatography [conductivity detector (Hitachi High-Tech Science Corporation, L-2470), pump (Hitachi High-Tech Science Corporation, L-2130), analytical column (Hitachi High-Tech Fielding Corporation, product name #2740 (4.6 mm I.D. × 150 mm)), column oven (Hitachi High-Tech Science Corporation, L-2350)] under the following conditions: column temperature: 40°C, mobile phase: distilled water containing 2.5 mol / L tris(hydroxymethyl)aminomethane and 2.3 mol / L phthalic acid, flow rate: 1.5 mL / min.

[0062] <Hazen unit color number> The Hazen unit color number of the wet cake of 5-sulfoisophthalic acid was measured by adding 50 mL of a 50 mass % aqueous solution of 5-sulfoisophthalic acid to a 50 mL Nessler tube and using water as a blank with a Hazen measuring instrument (manufactured by Tintometer, model: Nessleriser 2150).

[0063] <Average particle size> The average particle size of the wet cake of 5-sulfoisophthalic acid was measured by averaging the Feret diameters of more than 1,000 crystals using a microscope (Keyence Corporation, Model: VHX-500F) and dispersing the crystals by applying ultrasonic waves for 30 seconds using an ultrasonic cleaner (SND Corporation, Model: US-705) with the filtrate obtained by filtering the wet cake for 5-sulfoisophthalic acid monohydrate or a saturated aqueous solution of 5-sulfoisophthalic acid tetrahydrate as a dispersion solvent.

[0064] <Powder X-ray diffraction> The crystalline phase of the wet cake of 5-sulfoisophthalic acid was confirmed by powder X-ray diffraction analysis using a fully automated multipurpose X-ray diffractometer (Rigaku Corporation, model: SmartLab).

[0065] <Single crystal X-ray structure analysis> The crystal structure of the wet cake of 5-sulfoisophthalic acid was determined by single crystal structure analysis using a curved imaging plate single crystal automatic X-ray structure analyzer (Rigaku Corporation, model: R-AXIS RAPID IIα).

[0066] <Thermogravimetry (TG)> Thermogravimetry (TG) of the wet cake of 5-sulfoisophthalic acid was carried out by the following method: First, 10 to 12 mg of the wet cake was precisely weighed into an alumina open-type sample container, and the temperature was raised from 20°C to 180°C at a rate of 2°C / min while feeding nitrogen at a flow rate of 200 mL / min using a simultaneous differential thermal and thermogravimetry analyzer (manufactured by Hitachi High-Tech Science Corporation, model: TG / DTA6200).

[0067] Example 1 Isophthalic acid (300g) was added to 28% by mass fuming sulfuric acid (822g) that was 2.74 times by mass relative to the isophthalic acid while stirring, and the mixture of isophthalic acid and fuming sulfuric acid was kept at 190°C for 2 hours, and then cooled to 100°C. Next, the reaction mixture was dropped into water (558g) that was 1.86 times by mass relative to the isophthalic acid while stirring, and after cooling to 30°C, the precipitate was centrifuged at a rotation speed of 5000 rpm for 15 minutes. The obtained columnar crystals were hydrated crystals of 5-sulfoisophthalic acid (489g), and as a result of evaluation with an automatic titrator, the content of 5-sulfoisophthalic acid in the hydrated crystals was 89% by mass and the content of sulfuric acid was 3% by mass. The yield from isophthalic acid was 98%.

[0068] Next, the hydrated crystals of 5-sulfoisophthalic acid (163 g) obtained by the above operation were added to 20°C water (61 g) of 0.42 times the mass of the 5-sulfoisophthalic acid in the hydrated crystals while stirring, and the suspension was kept at 20°C for 3 hours. At this time, the crystals of 5-sulfoisophthalic acid changed to columnar crystals 18 minutes after the start of the incubation. After keeping the suspension at 20°C for 3 hours, the suspension was centrifuged at a rotation speed of 5000 rpm for 15 minutes. The obtained columnar crystals were hydrated crystals of 5-sulfoisophthalic acid (73 g), and had an average particle size of 314 μm. As a result of evaluation with an automatic titration device, the content of 5-sulfoisophthalic acid in the hydrated crystals was 77% by mass, and as a result of evaluation with ion chromatography, the content of sulfuric acid in the hydrated crystals was 0.1% by mass. The yield from isophthalic acid was 38%. The hydrated crystals were dissolved in water to obtain an aqueous solution having a concentration of 50% by mass of 5-sulfoisophthalic acid. The Hazen color number of the aqueous solution was 140.

[0069] The powder X-ray diffraction spectrum of this hydrated crystal is shown in Figure 1. In the powder X-ray diffraction spectrum, this hydrated crystal had characteristic peaks at the following 2θ angles: 18.1±0.2°, 20.2±0.2°, 24.6±0.2°, 27.3±0.2°, 30.5±0.2°, and 31.9±0.2°.

[0070] Comparative Example 1 In the production process of Example 1, the reaction mixture was cooled to 30° C., and the precipitate was centrifuged to obtain hydrated crystals of 5-sulfoisophthalic acid containing 3% by mass of sulfuric acid. The average particle size of the hydrated crystals was measured and found to be 30 μm. The Hazen color scale of an aqueous solution of 5-sulfoisophthalic acid with a concentration of 50% by mass obtained by dissolving the hydrated crystals in water was 240.

[0071] The single crystal X-ray structure analysis of this hydrated crystal showed that it had the following unit cell dimensions at 173K: a = 14.1445(14) Å; b = 10.9611(10) Å; c = 13.5039(13) Å; β = 98.727(7)°; unit cell volume: V = 2069.4(3) Å; number of asymmetric units in the lattice: Z = 8; and space group: C2 / c. The molecular structure of this hydrated crystal obtained by single crystal X-ray structure analysis is shown in the ORTEP diagram in Figure 9, and the molecular packing diagram in Figure 10. The hydrated crystal was 5-sulfoisophthalic acid monohydrate.

[0072] The powder X-ray diffraction spectrum of this hydrated crystal is shown in Figure 8. In the powder X-ray diffraction spectrum, this hydrated crystal had characteristic peaks at the following 2θ angles: 10.4±0.2°, 11.8±0.2°, 21.1±0.2°, 25.3±0.2°, 32.7±0.2°, and 42.1±0.2°.

[0073] Moreover, the results of thermogravimetry (TG) are shown in FIG.

[0074] Example 2 In the production process of Example 1, the reaction mixture was cooled to 30°C, and the precipitate was centrifuged to obtain hydrated crystals of 5-sulfoisophthalic acid monohydrate (163 g). The hydrated crystals were then added to water (58 g) with a mass of 0.40 times the mass of 5-sulfoisophthalic acid in the hydrated crystals while stirring. The temperature was raised to 70°C, and the solution was kept at the same temperature for 1 hour to completely dissolve the crystals of 5-sulfoisophthalic acid monohydrate. When the solution was cooled to 47°C, plate-like crystals were precipitated. The solution was further cooled, and when the solution reached 35°C, the hydrated crystals of 5-sulfoisophthalic acid with a sulfuric acid content of 0.1% by mass obtained in Example 1 (18 mg) were added. Cooling was continued, and the crystals changed to columnar crystals at 34°C. The columnar crystals obtained by further cooling to 15°C and centrifugal filtration at a rotation speed of 5000 rpm for 15 minutes were 5-sulfoisophthalic acid hydrate crystals (94 g) with an average particle size of 1222 μm. As a result of evaluation with an automatic titrator, the content of 5-sulfoisophthalic acid in the hydrate crystals was 76 mass%, and as a result of evaluation with ion chromatography, the content of sulfuric acid in the hydrate crystals was 0.1 mass%. The yield from isophthalic acid was 49%.

[0075] The hydrated crystals were dissolved in water to obtain an aqueous solution having a concentration of 50% by mass of 5-sulfoisophthalic acid. The Hazen color number of the aqueous solution was 15.

[0076] The single crystal X-ray structure analysis of this hydrated crystal showed that it had the following unit cell dimensions at 173K: a = 7.139(2) Å; b = 9.490(3) Å; c = 10.535(3) Å; α = 70.999(7)°; β = 77.158(7)°; γ = 85.530(8)°; unit cell volume: V = 658.0(3) Å; number of asymmetric units in the lattice: Z = 2; and space group: P-1. The molecular structure of this hydrated crystal obtained by single crystal X-ray structure analysis is shown in the ORTEP diagram in Figure 3, and the molecular packing diagram in Figure 4. This hydrated crystal was identified as 5-sulfoisophthalic acid tetrahydrate.

[0077] The powder X-ray diffraction spectrum of this hydrated crystal is shown in Figure 2. In the powder X-ray diffraction spectrum, this hydrated crystal had characteristic peaks at the following 2θ angles: 18.2±0.2°, 20.3±0.2°, 24.7±0.2°, 27.4±0.2°, 30.5±0.2°, and 32.0±0.2°.

[0078] From the results of X-ray analysis of Examples 1 and 2, both hydrated crystals were found to be 5-sulfoisophthalic acid tetrahydrate.

[0079] Moreover, the results of thermogravimetry (TG) are shown in FIG.

[0080] Comparative Example 2 Using isophthalic acid (300 g), 28% by mass fuming sulfuric acid (822 g), which is 2.74 times by mass relative to the isophthalic acid, and water (521 g), which is 1.74 times by mass, 5-sulfoisophthalic acid monohydrate (497 g) was obtained as hydrated crystals in the same manner as in Comparative Example 1. As a result of evaluation with an automatic titrator, the content of the hydrated crystals was 88% by mass of 5-sulfoisophthalic acid and 4% by mass of sulfuric acid, and the yield from isophthalic acid was 98%. The average particle size was measured and found to be 35 μm. The Hazen color unit number of an aqueous solution of 5-sulfoisophthalic acid with a concentration of 50% by mass obtained by dissolving the hydrated crystals in water was 250.

[0081] 〔summary〕 Table 1 shows the purity of 5-sulfoisophthalic acid, the content of sulfuric acid, as well as the Hazen color number and average particle size of the 5-sulfoisophthalic acid hydrates obtained in the Examples and Comparative Examples.

[0082] [Table 1]

[0083] As shown in Table 1, it was confirmed that the 5-sulfoisophthalic acid hydrate obtained in Examples 1 and 2 was a tetrahydrate, and that the 5-sulfoisophthalic acid hydrate obtained in Comparative Examples 1 and 2 was a monohydrate. The amount excluding the 5-sulfoisophthalic acid purity and sulfuric acid content in the crystals of 5-sulfoisophthalic acid monohydrate obtained in Comparative Examples 1 and 2 was 8% by mass, and the amount excluding the 5-sulfoisophthalic acid purity and sulfuric acid content in the crystals of 5-sulfoisophthalic acid tetrahydrate obtained in Examples 1 and 2 was about 23% to 24% by mass. It is understood that the difference between 8% by mass and about 23% to 24% by mass is due to the difference in the content of water of crystallization.

[0084] The average particle size of the crystals of 5-sulfoisophthalic acid tetrahydrate obtained in Examples 1 and 2 was larger than that of the crystals of 5-sulfoisophthalic acid monohydrate obtained in Comparative Examples 1 and 2. In Examples 1 and 2, 5-sulfoisophthalic acid tetrahydrate had better filterability than 5-sulfoisophthalic acid monohydrate. This is considered to be due to the larger particle size. In addition, the crystals of 5-sulfoisophthalic acid tetrahydrate had a significantly reduced sulfuric acid content and reduced coloration compared to the crystals of 5-sulfoisophthalic acid monohydrate. [Industrial Applicability]

[0085] 5-Sulfoisophthalic acid is industrially very useful as a raw material for metal salts of 5-sulfoisophthalic acid used as additives in polymer production, alkyl esters of 5-sulfoisophthalic acid used as modifiers for polyesters, etc. In addition, since sulfuric acid contained as an impurity in 5-sulfoisophthalic acid has an undesirable effect on these applications as additives and modifiers, the 5-sulfoisophthalic acid of the present application, which has a reduced sulfuric acid content, is industrially very useful.

Claims

1. A crystal of 5-sulfoisophthalic acid tetrahydrate, the crystal space group of which is P-1 (where "-" indicates an overline of 1), with unit cell constants of a = 7.139(2) Å, b = 9.490(3) Å, c = 10.535(3) Å, α = 70.999(7)°, β = 77.158(7)°, and γ = 85.530(8)°.

2. The crystal of 5-sulfoisophthalic acid tetrahydrate according to claim 1, having a sulfuric acid content of 2.0% by mass or less.

3. A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate, comprising the step of suspending a crude product containing crystals of 5-sulfoisophthalic acid monohydrate in water to obtain crystals of 5-sulfoisophthalic acid tetrahydrate, The crystals of 5-sulfoisophthalic acid monohydrate have unit cell dimensions: a=14.1445(14) Å; b=10.9611(10) Å; c=13.5039(13) Å; β=98.727(7)°; unit cell volume: V=2069.4(3) Å; number of asymmetric units in the lattice: Z=8; and are in the space group C2 / c; when measured at 173K, The crystal of 5-sulfoisophthalic acid tetrahydrate has a crystal space group of P-1 (where "-" indicates an overline of 1), and the lattice constants of the unit cell are a = 7.139(2) Å, b = 9.490(3) Å, c = 10.535(3) Å, α = 70.999(7)°, β = 77.158(7)°, and γ = 85.530(8)°.

4. The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to claim 3, comprising a step of suspending a crude product containing crystals of 5-sulfoisophthalic acid monohydrate in water and incubating the suspension at 34° C. or lower for 5 minutes or longer.

5. The amount of water in which the crude product is suspended is 0.19 to 0.60 times by mass relative to the amount of 5-sulfoisophthalic acid (excluding water of crystallization) in the crude product. The method for producing crystals of 5-sulfoisophthalic acid tetrahydrate according to claim 3 or 4.

6. A method for producing crystals of 5-sulfoisophthalic acid tetrahydrate, comprising a step of crystallizing a crude product containing crystals of 5-sulfoisophthalic acid monohydrate with water, A step of dissolving a crude product containing crystals of 5-sulfoisophthalic acid monohydrate in water at a temperature of 34° C. to 104° C.; cooling the aqueous solution obtained in the previous step; and a step of adding seed crystals of 5-sulfoisophthalic acid tetrahydrate to the aqueous solution at a temperature of 38° C. or lower and in a state of being supersaturated or in which crystals have precipitated, thereby obtaining crystals of 5-sulfoisophthalic acid tetrahydrate, The crystals of 5-sulfoisophthalic acid monohydrate have unit cell dimensions: a=14.1445(14) Å; b=10.9611(10) Å; c=13.5039(13) Å; β=98.727(7)°; unit cell volume: V=2069.4(3) Å; number of asymmetric units in the lattice: Z=8; and are in the space group C2 / c; when measured at 173K, The crystals and seed crystals of 5-sulfoisophthalic acid tetrahydrate have a crystal space group of P-1 (where "-" indicates an overline of 1), and the lattice constants of the unit cell are a = 7.139(2) Å, b = 9.490(3) Å, c = 10.535(3) Å, α = 70.999(7)°, β = 77.158(7)°, and γ = 85.530(8)°.

Citation Information

Patent Citations

  • Purifying sulpho-phthalic acid contg. water and sulphuric acid - by washing with (cyclo)aliphatic ketone(s) opt. mixed with (chloro)hydrocarbon(s)

    DE2804330A1

  • JP1963025670B

  • Alkyl sulfo-substituted aromatic carboxylate and method for producing the same

    JP2004331527A

  • Method for producing alkali salt of alkyl sulfo-substituted aromatic carboxylate

    JP2005145836A

  • Use of an acetic acid / water mixed solvent for preparing low-sulfate 5-sulfisophthalic acid monolithium salt from 5-sulfisophthalic acid.

    JP2013508377A